Cardiac output changes during exercise in heart failure patients: focus on mid‐exercise. (17th November 2020) - Corrieri, Nicoletta; Del Torto, Alberico; Vignati, Carlo; Maragna, Riccardo; De Martino, Fabiana; Cellamare, Martina; Farina, Stefania; Salvioni, Elisabetta; Bonomi, Alice; Agostoni, Piergiuseppe
Abstract: Aims: Peak exercise oxygen uptake (VO2 ) and cardiac output (CO) are strong prognostic indexes in heart failure (HF) but unrelated to real‐life physical activity, which is associated to submaximal effort. Methods and results: We analysed maximal cardiopulmonary exercise test with rest, mid‐exercise, and peak exercise non‐invasive CO measurements (inert gas rebreathing) of 231 HF patients and 265 healthy volunteers. HF patients were grouped according to exercise capacity (peak VO2 < 50% and ≥50% pred, Groups 1 and 2). To account for observed differences, data regarding VO2, CO, stroke volume (SV), and artero‐venous O2 content difference [ΔC(a‐v)O2 ] were adjusted by age, gender, and body mass index. A multiple regression analysis was performed to predict peak VO2 from mid‐exercise cardiopulmonary exercise test and CO parameters among HF patients. Rest VO2 was lower in HF compared with healthy subjects; meanwhile, Group 1 patients had the lowest CO and highest ΔC(a‐v)O2 . At mid‐exercise, Group 1 patients achieved a lower VO2, CO, and SV [0.69 (interquartile range 0.57–0.80) L/min; 5.59 (4.83–6.67) L/min; 62 (51–73) mL] than Group 2 [0.94 (0.83–1.1) L/min; 7.6 (6.56–9.01) L/min; 77 (66–92) mL] and healthy subjects [1.15 (0.93–1.30) L/min; 9.33 (8.07–10.81) L/min; 87 (77–102) mL]. Rest to mid‐exercise SV increase was lower in Group 1 than Group 2 ( P = 0.001) and healthy subjects ( P < 0.001). At mid‐exercise, ΔC(a‐v)O2 was higher in Group 2 [13.6 (11.8–15.4) mL/100 mL] vs. healthy patients [11.6 (10.4–13.2) mL/100 mL] ( P = 0.002) but not different from Group 1 [13.6 (12.0–14.9) mL/100 mL]. At peak exercise, Group 1 patients achieved a lower VO2, CO, and SV than Group 2 and healthy subjects. ΔC(a‐v)O2 was the highest in Group 2. At multivariate analysis, a model comprising mid‐exercise VO2, carbon dioxide production (VCO2 ), CO, haemoglobin, and weight predicted peak VO2, P < 0.001. Mid‐exercise VO2 and CO, haemoglobin, and weight added statistically significantly to the prediction, P < 0.050. Conclusions: Mid‐exercise VO2 and CO portend peak exercise values and identify severe HF patients. Their evaluation could be clinically useful.